Case Report: A thrombosis of ductus arteriosus aneurysm involving the left pulmonary artery in a full-term newborn with isolated right ventricular hypoplasia - Krasic, Stasa; Djorovic, Nevena; Dizdarevic, Ivan; Topic, Vesna; Ilic, Nikola; Sarajlija, Adrijan; Aleksic, Dragana; Vukomanovic, Vladislav (Frontiers in Pediatrics, 2025)
BackgroundThrombosis of ductus arteriosus aneurysm (DAA) is a well-known complication of DAA that can lead to vascular obstruction or thromboembolic events.Case reportA full-term male newborn presented with isolated right ventricular hypoplasia (IRVH). Follow-up echocardiography at 19 days of life revealed a pedunculated mass, suggesting a thrombus partially obstructing the left pulmonary artery (LPA). The patient remained clinically stable but was admitted to the neonatal intensive care unit for close monitoring. CT and MRI confirmed DAA thrombosis involving LPA. Due to a lack of resolution with conservative treatment, the patient underwent a thrombectomy and resection of the ductus arteriosus (DA). The postoperative course was uneventful, and the follow-up echocardiography showed normalisation of the right ventricular cavity and no residual thrombus.ConclusionThis case highlights the importance of early detection and investigation in neonates with echocardiographic findings of intrauterine ductus arteriosus closure, stenosis, or DA closure in the first 12 h of life to prevent life-threatening complications.